Bioflocculant production from untreated corn stover using Cellulosimicrobium cellulans L804 isolate and its application to harvesting microalgae - Liu, Weijie (Biotechnol Biofuels, 2015)
BACKGROUND: Microalgae are widely studied for biofuel production. Nevertheless, harvesting step of biomass is still a critical challenge. Bioflocculants have been applied in numerous applications including the low-cost harvest of microalgae. A major bottleneck for commercial application of bioflocculant is its high production cost. Lignocellulosic substrates are abundantly available. Hence, the hydrolyzates of rice stover and corn stover have been used as carbon source to produce the bioflocculant in previous studies. However, the hydrolyzates of biomass required the neutralization of pH before the downstream fermentation processes, and the toxic by-products produced during hydrolysis process inhibited the microbial activities in the subsequent fermentation processes and contaminated the bioflocculant product. Therefore, strains that can secrete plant cell-wall-degrading enzymes and simultaneously produce bioflocculants through directly degrading the lignocellulosic biomasses are of academic and practical interests. RESULTS: A lignocellulose-degrading strain Cellulosimicrobium cellulans L804 was isolated in this study, which can produce the bioflocculant MBF-L804 using untreated biomasses, such as corn stover, corn cob, potato residues, and peanut shell. The effects of culture conditions including initial pH, carbon source, and nitrogen source on MBF-L804 production were analyzed. The results showed that over 80 % flocculating activity was achieved when the corn stover, corn cob, potato residues, and peanut shell were used as carbon sources and 4.75 g/L of MBF-L804 was achieved under the optimized condition: 20 g/L dry corn stover as carbon source, 3 g/L yeast extract as nitrogen source, pH 8.2. The bioflocculant MBF-L804 contained 68.6 % polysaccharides and 28.0 % proteins. The Gel permeation chromatography analysis indicated that the approximate molecular weight (MW) of MBF-L804 was 229 kDa. The feasibility of harvesting microalgae Chlamydomonas reinhardtii and Chlorella minutissima using MBF-L804 was evaluated. The highest flocculating efficiencies for C. reinhardtii and C. minutissima were 99.04 and 93.83 %, respectively. CONCLUSIONS: This study shows for the first time that C. cellulans L804 can directly convert corn stover, corn cob, potato residues and peanut shell into the bioflocculants, which can be used to effectively harvest microalgae. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-015-0354-4) contains supplementary material, which is available to authorized users.